The Use of Dremina as a Digital Storytelling Tool to Improve Students’ Motivation in Learning English - Nazli Fahada; Chairunnissa Chairunnissa (ALACRITY : Journal of Education, 2025)
This study investigates the use of Dremina as a digital storytelling tool to enhance students’ motivation in learning English at MTs Al Washliyah Batang Serangan. Using a qualitative descriptive design, data were collected through classroom observations, semi-structured interviews, and analysis of students’ Dremina-based storytelling projects. The findings show that Dremina significantly increased student engagement, participation, and confidence in expressing ideas in English. Its features, such as visual customization, voice recording, and interactive editing, supported students in organizing meaning and developing creativity. The results align with Vygotsky’s sociocultural theory, Self-Determination Theory, and the Cognitive Theory of Multimedia Learning, indicating that Dremina fosters autonomy, competence, and multimodal literacy. Overall, the study concludes that digital storytelling through Dremina provides an effective, motivating, and learner-centered approach to English instruction. The findings also highlight implications for teachers seeking innovative strategies to improve language learning outcomes.